Metode Penyisihan Piutang Tak Tertagih Pada Produk Qardh Di Bank Pembiayaan Rakyat Syariah Barokah Dana Sejahtera Yogyakarta Periode 2017 - Daningrum, Januar; Mikhriani, Mikhriani (Jurnal Bisnis : Teori dan Implementasi, 2018)
The giving of credit is one of the products that become a mainstay for the bank. Not a few banks use a credit as a means to attract customers or branding. The crediting process involves two parties, namely the bank as the creditor and the customer as the debtor. Lending or credit will increase the profit for the bank, but if it can’t be managed properly will cause losses. Customers who are experiencing difficulties in paying installments to ultimately experience a default. This will result in bad debts for banks. If it is not handled seriously it will endanger the liquidity of the bank and end up in bankruptcy